Effectiveness of Recognition to the Performance of Rank-And-File Employees of McDonald’s Branch in SM Novaliches, Quezon City: Vol.4, No.1 (Ascendens Asia Singapore – Bestlink College of the Philippines Journal of Multidisciplinary Research, 2024)
The purpose of this study is to determine the effectiveness of recognition on the performanceof rank-and-file employees in McDonald’s Sm Novaliches Branch in terms of recognition,rewards, promotion, and employee relations. Performances: quality of output, employeecommitment, employee speed. The researchers are motivated to conduct this study entitled“Effectiveness of Recognition to the Performance of Rank-and-file Employees of McDonald’sBranch in SM Novaliches, Quezon City” to give an Action Plan to the problem of theeffectiveness the employee performance of having not appreciated by the company in thecase of doing their job well but not having a recognition. This study will benefit both theemployees and the organization. Employees can seek opportunities for their careers as theycan use their knowledge, skills, and expertise in the food industry. Rank-and-file not only wantgood salaries and benefits, but they want to be treated fairly as well, to make a strongcontribution to the association through their hard work, and to be valued and appreciated fortheir hardship.The result of this study reveals the effectiveness of recognition on the performance of rank-and-file employees in terms of recognition, rewards, promotion, and employee relations.Performances, quality of output, employee commitment, and employee speed are effective.The problem encountered in terms of favoritism and kinship, and there is an action plan thatcan be proposed in the sustainability of effectiveness of recognition to the performance whichis store rotation practices of management staffs or crew and develop an active anti- kinship &anti-favoritism policy then conduct a follow-up leadership training for the management.This study recommended that management continue to implement recognition and focus ontheir performance. Such as recognition, rewards, promotion, and employee relations.Performances: quality of output, employee commitment, employee speed. The rank-and-fileperformance will be a strong basis for management to recognize them.
Keywords: Business